Functional crosstalk of prejunctional receptors on the modulation of noradrenaline release in mesenteric vessels: A differential study of artery and vein - Carlos Talaia (2011)
The role of angiotensin II receptors, bradykinin receptors and beta-adrenoceptors in the modulation of noradrenaline release and the influence of alpha(2)-autoinhibition in these effects was investigated in the mesenteric artery and vein. Rings of mesenteric vessels of male Wistar rats were labelled with [(3)H]noradrenaline and the effects of modulators on tritium overflow evoked by 100 pulses at 2 Hz (marked alpha(2)-autoinhibition) and by 20 pulses at 50 Hz or 100 pulses at 2 Hz plus yohimbine (1 mu M; reduced alpha(2)-autoinhibition) were evaluated. Angiotensin II and bradykinin enhanced noradrenaline release evoked by 100 pulses at 2 Hz, in a concentration-dependent manner, in both vessels. These effects were attenuated under conditions of reduced alpha(2)-autoinhibition. The attenuation was partially reversed by activation of adenosine A(1) receptors in both vessels and by activation of P2Y receptors in the vein. Isoprenaline and the selective beta(2)-adrenoceptor agonist formoterol enhanced tritium overflow independently of alpha(2)-autoinhibition in the vein. In the artery, the enhancement by formoterol was only observed under reduced alpha(2)-autoinhibition. Pharmacological characterization of the beta-adrenoceptors indicated that in the artery the effect of isoprenaline was mediated by the beta(1)-subtype under marked alpha(2)-autoinhibition and by the beta(2)-subtype under reduced alpha(2)-autoinhibition whereas in the vein the effect was independent of alpha(2)-autoinhibition. The results indicate that alpha(2)-autoinhibition is a key determinant of the magnitude of facilitation caused by angiotensin II and bradykinin in both types of mesenteric vessels and regulates the effects mediated by beta(1)-and beta(2)-adrenoceptors which co-exist in the artery.